Strategies for Implementing Social and Pedagogical Competencies of Islamic Religious Education Teachers in Overcoming Student Learning Difficulties at UPT SDN 74 Bolang Enrekang Regency - Sukriati Sukriati; Syarifuddin Yusuf; Muhammad Naim; Andi Fitriani Djollong; Suredah Hamid (ANTHOR: Education and Learning Journal, 2026)
This study aims to analyze the social and pedagogical competencies of Islamic Religious Education (PAI) teachers in overcoming student learning difficulties at UPT SDN 74 Bolang, Enrekang Regency. Employing a qualitative descriptive approach with a case study method, data were collected through participatory observation, in-depth interviews, and documentation involving the principal, two PAI teachers, four homeroom teachers, and eight students. The findings reveal that: (1) The social and pedagogical competencies of PAI teachers play a vital role in creating a conducive learning environment through empathic communication, personal approaches, and differentiated instruction; (2) Student learning difficulties are multidimensional, encompassing cognitive difficulties in understanding abstract religious concepts and Arabic readings, as well as affective and psychomotor challenges influenced by internal and external factors; (3) Key supporting factors include teachers' adaptive competencies, school policy support, and inter-teacher collaboration, while barriers include student ability heterogeneity, limited time, minimal learning media, administrative burden, and low parental involvement; (4) The implementation of personal, active-contextual, and collaborative strategies proved effective in enhancing students' comprehension and participation. This study recommends continuous technology-based teacher competency development and a holistic approach involving schools, families, and the social environment.